Scrolling, sharing, shaping: cognitive and behavioral effects of SNS communication on Japan’s national image in China - Tengfei Zhang (Humanities & Social Sciences Communications)
Abstract National images today are shaped not only by state-led narratives but also through daily interactions on social networking sites, where passive consumption and active expression converge to influence public perceptions. This study investigates how message reception and expression affect Chinese audiences’ image of Japan. We examine how cognitive responses mediate the influence of SNS engagement on behavioral intentions by integrating a communication mediation framework with the bidirectional message effects model. Our findings indicate a dichotomy: while message reception fosters a positive evaluation of Japan, message expression elicits skepticism and cautious intentions toward Japan. It is thus imperative to expand beyond reception-oriented models to encompass the reciprocal nature of online communication, contesting the prevailing perspective that excessively highlights the role of digital communication in augmenting soft power. The study’s implications are noteworthy for digital and public diplomacy endeavors, suggesting practitioners should consider the interaction between passive and active engagement on SNS.